Teachers’, principals’ and non-educational professionals’ representations of multicultural and intercultural education - Pincheira Muñoz, Luis Enrique (Transformación, 2024)
Objective: The paper describes the findings of a doctoral dissertation aimed at interpreting the cultural inclusion of immigrants in Chilean schools and teachers’, principals’ and non-educational professionals’ representations of multicultural and intercultural education.Methods: The research follows a qualitative paradigm with the prevalence of descriptive and interpretative tools to analyze the educative agents’ cultural background. A case study of collective or multiple characters was carried out for understanding proximity, distance, similarities, and dissenting opinions; likewise, interviews were used to collect information.Results: The findings reflect a poor theoretical background knowledge on the part of teachers, principals and non-educational professionals to distinguish between multicultural and intercultural models, their assessment of the limit role played by Chilean Ministry of Education and local authorities, usually focused on measuring students’ learning through standardized tests, and the limited attention to immigrant students inclusion in the school community. Conclusion: The management of the inclusion of immigrant students to the school community is facing difficulties that demand a professional development of teachers, principals and non-educational professional to lead education in the multicultural and intercultural context.
Keywords: multicultural education; intercultural education; school community